2021
DOI: 10.1177/15353702211023359
|View full text |Cite
|
Sign up to set email alerts
|

Shear type and magnitude affect aortic valve endothelial cell morphology, orientation, and differentiation

Abstract: Valvular endothelial cells line the outer layer of heart valves and can withstand shear forces caused by blood flow. In contrast to vascular endothelial cells, there is limited amount of research over valvular endothelial cells. For this reason, the exact physiologic behavior of valvular endothelial cells is unclear. Prior studies have concluded that valvular endothelial cells align perpendicularly to the direction of blood flow, while vascular endothelial cells align parallel to blood flow. Other studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Compare these results to a study by Kang et al, which showed that shear stress of 3–5.3 dyne/cm 2 stimulated sprout formation by cells cultured in three dimensions and that 12 dyne/cm 2 inhibited growth 13 . Shear stress values used to study endothelial cell responses range from 0.1 to 50 dyne/cm 2 14–16 . Even studies using 100 dyne/cm 2 17 can be found.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Compare these results to a study by Kang et al, which showed that shear stress of 3–5.3 dyne/cm 2 stimulated sprout formation by cells cultured in three dimensions and that 12 dyne/cm 2 inhibited growth 13 . Shear stress values used to study endothelial cell responses range from 0.1 to 50 dyne/cm 2 14–16 . Even studies using 100 dyne/cm 2 17 can be found.…”
Section: Introductionsupporting
confidence: 68%
“…13 Shear stress values used to study endothelial cell responses range from 0.1 to 50 dyne/cm 2 . [14][15][16] Even studies using 100 dyne/cm 217 can be found. The range in shear stresses used for in vitro studies and the variable responses provoke additional questions about the physiological relevance of the assays.…”
mentioning
confidence: 99%
“…(16) demonstrated that cell size is modulated by shear flow. Longer exposure to shear flow decreases cell area, while increasing cell aspect ratio across longer (approx.…”
Section: Resultsmentioning
confidence: 99%
“…As shear stress increases, endothelial cells polarise against flow, however, this phenotype is ablated with EC senescence. In addition, Deb et al (14) demonstrated that cell size is modulated by shear flow. Longer exposure to shear flow decreases cell area, while increasing cell aspect ratio across longer (approx.…”
Section: Shape Asymmetriesmentioning
confidence: 99%
See 1 more Smart Citation